Design and Implementation of a Mobile Application for Disseminating Information among Nigerian Farmers - Boyinbode, OK; Osagiede, NA (International Journal of Computer Sciences and Engineering, 2020)
Traditionally, farmers in Nigeria, mostly get agricultural information through verbal word from families and friends and this has led to stagnation in agricultural development, as many farmers are not exposed to the latest developments in agriculture. Due to advancements in ICT, there are better ways of disseminating information to large number of farmers instantly. This paper describes the design and implementation of a mobile application for disseminating information among Nigerian farmers, thereby promoting interaction and collaboration. Farmers with access to internet or via SMS can get notifications of vital agricultural information through mobile application.